Perspectives on transitions away from donor assistance for health: a discrete choices experiment in Sri Lanka - Ipchita Bharali, MIDP; Wenhui Mao, PhD; Hanna Huffstetler, BA; Annahl Hoole, MD; Prasadini Perera, PhD; Osondu Ogbuoji, ScD (Elsevier, 2020)
Background: Since Sri Lanka transitioned to an upper-middle-income country in 2019, it is no longer eligible for concessional donor aid for health. Experiences of how donor transitions in the health sector were managed in Sri Lanka offer valuable insights to mitigate negative impacts of donor exits. In this study, we seek to understand preferences of in-country stakeholders for potential policy options to manage donor transitions. Methods: We conducted a discrete choice experiment with attributes and levels developed from 17 qualitative interviews conducted in Sri Lanka. The attributes (and levels) included were: (1) conducted transition readiness assessment (TRA) (Yes/No); (2) developed a national plan to manage the transition process (Yes/No); (3) ministry leading the transition (Ministry of Finance/Ministry of Health/both ministries); (4) post-transition funding (increasing domestic health budget allocations/encourage public health facilities to generate revenues/reduce wastage and improve efficiency; and (5) post-transition funding through loans (no loans/low interest concessional loans/ high interest commercial loans). We analysed data by fitting a Hierarchical Bayes model. Findings: We analysed data from 61 respondents; 36 (59%) were from government agencies, 12 (20%) from non-governmental organisations (NGOs), five (8%) from donor agencies, and eight (13%) from other sectors. Stakeholders showed a strong preference to conduct TRA (utilities: 45·47) and develop a national plan to manage transition (57·69). Stakeholders preferred the Ministry of Health to lead the transition process (12·05). Post-transition funding through loans emerged as most important (35%), followed by development of a national plan (23%), and type of post-transition funding (19%). Increased domestic health funding was the most preferred form of post-transition funding. Government and NGO stakeholders preferred not to take loans after transition from donor aid. Importance assigned to attributes also varied between stakeholder groups. Both government (39%) and the NGOs (38%) felt health sector funding through loans after transition was the most important attribute, while donors (30%) reported that they would prefer to develop a national plan to manage the transition process. Interpretation: Better planning and sustainable health sector funding choices emerged as most important factors for managing transitions in Sri Lanka. These findings are key to the improvement of transition preparation and planning, and donor-government coordination in Sri Lanka. While most discussions about country transitions from donor assistance for health occur at a supranational level, this study aims to highlight in-country stakeholder perspectives that can improve a country's preparation for, or response to, donor transitions, and improve transition planning and coordination. Funding: Duke Global Health Institute